Using natural experiments to improve public health evidence: a review of context and utility for obesity prevention - Melanie Crane; Erika Bohn-Goldbaum; Anne Grunseit; Adrian Bauman (BMC, 2020)
Abstract Background Natural experiments are increasingly valued as a way to assess the health impact of health and non-health interventions when planned controlled experimental research designs may be infeasible or inappropriate to implement. This study sought to investigate the value of natural experiments by exploring how they have been used in practice. The study focused on obesity prevention research as one complex programme area for applying natural experiment studies. Methods A literature search sought obesity prevention research from January 1997 to December 2017 and identified 46 population health studies that self-described as a natural experiment. Results The majority of studies identified were published in the last 5 years, illustrating a more recent adoption of such opportunities. The majority of studies were evaluations of the impact of policies (n = 19), such as assessing changes to food labelling, food advertising or taxation on diet and obesity outcomes, or were built environment interventions (n = 17), such as the impact of built infrastructure on physical activity or access to healthy food. Research designs included quasi-experimental, pre-experimental and non-experimental methods. Few studies applied rigorous research designs to establish stronger causal inference, such as multiple pre/post measures, time series designs or comparison of change against an unexposed group. In general, researchers employed techniques to enhance the study utility but often were limited in the use of more rigorous study designs by ethical considerations and/or the particular context of the intervention. Conclusion Greater recognition of the utility and versatility of natural experiments in generating evidence for complex health issues like obesity prevention is needed. This review suggests that natural experiments may be underutilised as an approach for providing evidence of the effects of interventions, particularly for evaluating health outcomes of interventions when unexpected opportunities to gather evidence arise.